2021
DOI: 10.3390/ijms22073488
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl-Methane Based Thyromimetic Inhibitors for Transthyretin Amyloidosis

Abstract: Thyromimetics, whose physicochemical characteristics are analog to thyroid hormones (THs) and their derivatives, are promising candidates as novel therapeutics for neurodegenerative and metabolic pathologies. In particular, sobetirome (GC-1), one of the initial halogen-free thyromimetics, and newly synthesized IS25 and TG68, with optimized ADME-Tox profile, have recently attracted attention owing to their superior therapeutic benefits, selectivity, and enhanced permeability. Here, we further explored the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…As mentioned in the introduction, the nature of neurodegenerative diseases, including Alzheimer’s disease, is largely related to amyloid Aβ42 [ 1 , 2 , 3 , 4 ]. At the same time, research of this amyloid is carried out in several directions, on the one hand, the toxicity of oligomers of this amyloid relative to brain cells is studied [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and on the other hand, its structure is explored [ 3 , 4 , 9 ]. One of the main questions: how does the structure of this peptide change when of L-amino acids are replaced by D-analog?…”
Section: Chiral Inversion (Ci) In Model Systems and The Possible CI R...mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the introduction, the nature of neurodegenerative diseases, including Alzheimer’s disease, is largely related to amyloid Aβ42 [ 1 , 2 , 3 , 4 ]. At the same time, research of this amyloid is carried out in several directions, on the one hand, the toxicity of oligomers of this amyloid relative to brain cells is studied [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and on the other hand, its structure is explored [ 3 , 4 , 9 ]. One of the main questions: how does the structure of this peptide change when of L-amino acids are replaced by D-analog?…”
Section: Chiral Inversion (Ci) In Model Systems and The Possible CI R...mentioning
confidence: 99%
“…The choice of NSAIDs is not accidental, since the derivatives of these drugs are now being tested as inhibitor of γ-secretase-a complex of enzymes involved in the synthesis of Aβ42 from precursor of amyloid protein (APP) [18,19]. The mechanisms of the Aβ42 monomer action and its aggregated forms have been studied in cell models, while the primary cause of the formation of aggregates and their relationship with the inclusion of D-amino acids in biomolecules remains to be studied [3,4,[9][10][11]. This review describes first results on the influence of D-amino acids on the structure and properties, obtained in the study of model systems (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable data exists, providing a clear picture of the epidemiology in several countries in the European Community. Over time, new diagnostic and therapeutic approaches were adopted, reducing misdiagnosis and contributing to the quality and life expectancy of the affected patients [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…By combining nuclear magnetic resonance (NMR) spectroscopy, computational simulation, and biochemical assays, Kim et al [ 7 ] found that a small series of diphenyl-methane-based thyroid hormone analogs, including well-characterized lipid lowering agent Sobetirome [ 8 ], originally named GC-1, and recently developed TRβ selective agonist IS25 and its prodrug TG68 [ 9 , 10 ] act as TTR stabilizers and efficient suppressors of TTR aggregation, further expanding the potential of thyromimetics as multi-functional therapeutic molecules for TTR-related pathologies, including NDDs.…”
mentioning
confidence: 99%